Tripas revueltas. La muerte y el asco kantiano en la obra de Teresa Margolles - Arturi, Lucia (Revista de Teoría del Arte, 2018)
How to represent death in the artistic sphere? Can we talk about disgust in art? These are some of the questions that will guide this paper that explores in particular in the relationship between mexican artist Teresa Margolles´s photographic series Autorretratos en la morgue (1998) and philosopher Immanuel Kant´s notion of “disgust”.